(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article is devoted to the study of the opportunities and challenges of integrating artificial intelligence (AI) technologies into the oil and gas industry of Uzbekistan. In the context of global changes and pressure for sustainable development of the oil and gas sector, AI is a powerful tool for increasing efficiency, reducing costs and minimizing the negative impact on the environment. An analysis of the current state and approaches to the implementation of AI technologies in this key sector of the economy of Uzbekistan will highlight important areas for further research and practical applications.